Urbanization in China The Path to Harmony and Prosperity - Wei, Houkai; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book traces the history of urbanization in China and discusses major problems and challenges the country is facing as it undergoes a profound social transformation. The author argues that as China tries to build not just more but also better cities, i.e., cities that are not only economically competitive but also people- and environment-friendly, it should adopt urbanization strategies and policies that promote integrated development for both rural and urban areas, and coordination among otherwise disparate objectives - such as industrialization, ecological modernization, informatization and cultural heritage preservation - nationwide and at various scales.
Urbanization in China: History and Review -- The Essentials of the New China-Model Approach to Urbanization -- Strategic Thinking about Urbanization in China -- Resizing Towns and Cities in China -- Optimizing the Spatial Distribution of Cities in China -- Administrative Levels and Size Growth of Chinese Cities -- Spatial Expansion Effect of Urbanization in China -- Recommendations for Comprehensive Improvements in Urban Development and Management -- Pushing Institutional Innovation in Urbanization.
Keywords: Human geography; Social policy; Sustainability; Human Geography; Social Policy; Sustainability